Analisis Implementasi Media Pembelajaran dalam Meningkatkan Kualitas Pembelajaran Bahasa Indonesia di SD Negeri 1 Sangkaragung - Nengah Kadek Selamet; Ni Made Diantari Pratiyaksi; Ni Kade Indu Dewi Kumala Sari; Ni Luh Putu Divya Jyoti Mahardika; Ida Bagus Putrayasa (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
The phenomenon of using learning media at SD Negeri 1 Sangkaragung shows the challenges in improving the quality of Indonesian language learning, especially related to the effectiveness of the media used. This study aims to analyze the implementation of learning media in improving the quality of Indonesian language learning at the school. This research uses a qualitative approach with a case study design, which involves interviews, observation and documentation as data collection instruments. The research population included Indonesian language teachers, students, as well as the principal and school management. The sample was selected using purposive sampling technique, consisting of 5 teachers, 30 students, and the principal. The collected data were analyzed using thematic analysis, to identify the main themes that emerged from interviews, observations, and documentation. The results show that although the learning media used are quite varied, there are challenges in the quality of the media, especially learning videos which are still considered less attractive. In addition, limited facilities and teachers' skills in using learning media also become obstacles. Based on these findings, it is suggested that schools improve facilities and provide training to teachers in order to optimize the use of learning media in improving the quality of Indonesian language learning.